Pengaruh Intellectual Capital sebagai Competitive Advantage Perusahaan (Studi pada Perusahaan Petambangan Berbasis Batubara yang Terdaftar di Bursa Efek Indonesia) - Rizki - Gustadi; safaria siti (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2021)
Abstract : This study aims to examine and provide empirical evidence regarding the effect of intellectual capital (structural capital, human capital, and relational capital) on the company's competitive advantage. The object of research is coal-based mining companies listed on the Indonesia Stock Exchange (IDX) with a sample of 120 people who are employees with lower-level line managers, middle-level managers and top-level managers who work for these mining companies. The test was carried out using a hypothesis method which was analyzed and processed using IBM SPPS AMOS 26.0 (Analysis of Moment Structure). The results showed that the structural capital variable had no positive effect on the company's competitive advantage, while human capital and relational capital had a positive effect on the company's competitive advantage. "Relational capital has a positive effect on competitive advantage" The addition of other research variables that may be considered as a factor influencing the company's competitive advantage so that it better reflects the scope and interpretation of the actual conditions